2022
DOI: 10.1007/s00406-022-01427-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between chemosensory impairment with neuropsychiatric morbidity in post-acute COVID-19 syndrome: results from a multidisciplinary cohort study

Abstract: Preliminary methodologically limited studies suggested that taste and smell known as chemosensory impairments and neuropsychiatric symptoms are associated in post-COVID-19. The objective of this study is to evaluate whether chemosensory dysfunction and neuropsychiatric impairments in a well-characterized post-COVID-19 sample. This is a cohort study assessing adult patients hospitalized due to moderate or severe forms of COVID-19 between March and August 2020. Baseline information includes several clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 54 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…Studies assessing olfactory function in long-COVID have found that reported mental clouding was associated with more severe olfactory loss (Di Stadio et al, 2022). In addition, as in our study, olfactory loss was associated with cognitive impairment objectively assessed with neuropsychological tests of declarative memory (Damiano et al, 2022;Delgado-Alonso et al, 2022;Fiorentino et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies assessing olfactory function in long-COVID have found that reported mental clouding was associated with more severe olfactory loss (Di Stadio et al, 2022). In addition, as in our study, olfactory loss was associated with cognitive impairment objectively assessed with neuropsychological tests of declarative memory (Damiano et al, 2022;Delgado-Alonso et al, 2022;Fiorentino et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…However, this memory might be supported by other brain regions of the limbic system over time. Anosmia as a symptom in the long-COVID syndrome is frequently associated with the limbic system, both functionally (Damiano et al, 2022;Delgado-Alonso et al, 2022;Kay, 2022;Voruz et al, 2022;Yus et al, 2022) and structurally (Douaud et al, 2022;Morbelli et al, 2022). Therefore, a specific alteration of consolidation of procedural memory in long-COVID patients suffering from olfactory dysfunction is plausible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, declarative verbal memory, a memory system mainly supported by the medial temporal lobe including the hippocampus and other limbic system structures ( Catani et al, 2013 ), could be more impaired in long-COVID patients than other memory systems non-related to the limbic system function, such as procedural memory ( Llana et al, 2022a ). Olfactory dysfunction was associated not only with subjective memory complaints but also with objective verbal ( Damiano et al, 2022 ) and episodic ( Delgado-Alonso et al, 2022 ) memory performance, as well as with executive dysfunction and anxiety, but not depression ( Delgado-Alonso et al, 2022 ). Specifically, the study of Cecchetti et al (2022) found an association between dysgeusia and hyposmia during acute COVID-19 and increased vulneravility in declarative memory over time.…”
Section: Introductionmentioning
confidence: 99%
“…Furlan Damiano and Collaborators found a positive correlation between chemosensory problems (hypogeusia and parosmia) and cognitive dysfunction performing a neurobiological study on a statistical sample composed by 700 hospitalized mild-to-severe COVID-19 patients. The latter authors hypothesized that upon reaching the CNS, SARS-CoV-2 induces molecular and cellular cascade processes similar to those occurring in neurodegenerative diseases (Furlan Damiano et al 2022 ).…”
Section: Neurological Consequences Of Long-covid-19mentioning
confidence: 99%